Enhancing clinical effectiveness of pre-radiotherapy workflow by using multidisciplinary-cooperating e-control and e-alerts: A SQUIRE-compliant quality-improving study. Issue 24 (June 2017) - Lin, Yung-Hsiang; Hung, Shih-Kai; Lee, Moon-Sing; Chiou, Wen-Yen; Lai, Chun-Liang; Shih, Yi-Ting; Yeh, Pei-Han; Lin, Yi-An; Tsai, Wei-Ta; Hsieh, Hui-Ling; Chen, Liang-Cheng; Huang, Li-Wen; et al.
Abstract : Abstract: Radiotherapy (RT) is useful in managing cancer diseases. In clinical practice, early initiation of RT is crucial for enhancing tumor control. But, delivering precise RT requires a series of pre-RT working processes in a tight staff-cooperation manner. In this regard, using information system to conduct e-control and e-alerts has been suggested to improve practice effectiveness; however, this effect is not well defined in a real-world RT setting. We designed an information system to perform e-control and e-alerts for the whole process of pre-RT workflow to shorten processing time, to improve overall staff satisfaction, and to enhance working confidence. A quality-improving study conducted in a large RT center. Externally validated data were retrospectively analyzed for comparison before (from Sep. 2012 to Dec. 2012, n = 223) and after (from Sep. 2013 to Dec. 2013, n = 240) implementation of pre-RT e-control and e-alerts. Applying the e-control with delay-working e-alerts in pre-RT workflow was the main intervention. Nine workstations were identified in pre-RT workflow. The primary outcome measure was the processing time in each pre-RT workstations before and after implementing the e-control and e-alerts. Secondary measures were staff-working confidence and near-missing cases during the process of pre-RT workflow. After implementing e-control, overall processing time of pre-RT workflow was shortened from 12.2 days to 8.9 days ( P  < .001). Follow-up data (till Jul. 2016) showed a durable effect of 9.2 days, being still below the predefined threshold of <10 days. Using a multidisciplinary-cooperating information system is useful to conduct e-control and e-alerts in the whole process of pre-RT workflow. Clinical effectiveness, staff satisfaction, and working confidence are able to be enhanced obviously.